Faktor-Faktor Yang Mempengaruhi Financial Performance Dengan Earnings Management Sebagai Variabel Mediasi - William Martin, Henryanto Wijaya (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of this research is to examine empirical evidence the elements that influence financial performance with earnings management as mediating variable. The sample in this research was determined by purposive sampling method. The research conducted by taking 31 manufacturing companies with a family background. The result of this research shows that good corporate governance has a no significant positive effect on financial performance and significant negative effect on earnings management, earnings management has a no significant positive effect on financial performance, and earnings management can’t mediate effect of good corporate governance and corporate social responsibility on financial performance.